Health Education On Anxiety Levels In Projective Surgery Patients In Mokoyurli Buol Hospital - Irianti Ain (Chakra Brahmanda Lentera Institute, 2021)
Background: Nurses have the longest contact in handling patient problems and the role of nurses in their efforts to heal patients is very important. A nurse was required to know the patient's condition and needs. Objective of Knowing the Effect of Health Education on Anxiety Levels in Pre-appendectomy Surgeons in Mokoyurli Buol Hospital Methods: The design was used in the study was pre-experiment one group pre-post-test. The population was all patients with appendectomy. The sample size was 37 respondents using Simple random sampling technique. Independent variable of research was health education. The dependent variable was the level of anxiety. Data were collected using a questionnaire, then the data were analyzed using Wilcoxon test with a significance level of α <0.05. Results: The results showed that 15 respondents who experienced an anxiety level decreased, and 22 respondents had a level of anxiety remained after the intervention. Based on the results of statistical tests it was found that p = 0,000 with a <0,05, which means that there was an effect of Health Education on the Anxiety Level to Patients with Pre-Appendectomy Surgery at Mokoyurli Buol Hospital Conclusion: There was a decrease in anxiety levels after Health Education because of the provision in information and orientation readiness, thus reducing the causes of anxiety such as lack of information and make causing anxiety.